First person - Zariah Tolman (The Company of Biologists, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Zariah Tolman is first author on ' Elp1 is required for development of visceral sensory peripheral and central circuitry', published in DMM. Zariah conducted the research described in this article while an undergraduate research assistant in Frances Lefcort's lab at Montana State University, Bozeman, MT, USA. She graduated with a Master's degree under the advice of Mark Schure at Montana State University, investigating the mechanisms of how youth develop emotion regulation strategies and how emotional regulation relates to wellbeing.